Seeking refuge: findings from an evaluation of the 'running - other choices' refuge - Margaret S. Malloch (Scottish Journal of Residential Child Care)
Each year, a significant number of children and young people run away from, or are forced to leave, home. Research conducted by Wade (2001) estimated that approximately 9000 children run away from home in Scotland each year, with family conflict, abuse and problems at home cited as the main reasons. Rees and Lee (2005) indicated that one in six young runaways sleep rough, and one in 12 young runaways are hurt or harmed while running away. Alarmingly, Wade (2001) estimated that one in six young runaways in Scotland have been physically or sexually assaulted whilst away from home.